A systematic study on optoelectronic properties of Mn4+-activated Zr-based hexafluoride red phosphors X2ZrF6 (X = K, Na, Cs): first-principles investigation and prospects for warm-white LEDs applications. (9th November 2020) - Abbas, Zeesham; Azam, Sikander; Bashir, Azmat Iqbal; Marriam, Asia; Waqas, Muhammad; Alshahrani, Thamraa; Haq, Bakhtiar Ul
Abstract: The quest for developing energy-efficient and environment-friendly phosphors for lighting devices such as light-emitting diodes (LEDs) is on rise to meet the future energy challenges. In this connection, phosphor-converted white LEDs are promising candidates for the next generation state-of-the-art solid-state lighting technology to substitute the traditional lighting devices such as fluorescent lamps, incandescent lamps, halogen lamps, and backlights for liquid crystal displays. Hereby, we report a systematic analysis on the optoelectronics properties of Zr-based Mn 4+ -activated phosphors X2 ZrF6 (X = K, Na, Cs) for potential optoelectronics and photoluminescence device applications such as LEDs. For the comparative analysis of the first-principles calculations based on full-potential linearized augmented plane wave DFT procedure, we employed spin polarized GGA and GGA + U scheme of exchange and correlation energy potentials. In contrast to parent X2 ZrF6 compounds, the band gaps of the Mn-doped X2 MnF6 compounds have been lowered considerably. The improvement on band-gap values with GGA + U method reaffirms the famous drawback of GGA-based DFT methods regarding the underestimation of band gaps in highly correlated systems. For the prospects of materials regarding optoelectronics and photoluminescence applications, we first time report a detailed systematic analysis of optical properties such as dielectric functions, energy loss function, reflectivity, absorption coefficient, refractive index and optical conductivity. The materials are weakly photons reflector in IR and visible regions while they are strong photons absorbers in the UV region. In the absence of experimental evidences, indirect evidence of the wide band-gaps of K2 ZrF6 and Na2 ZrF6 compounds is ascertained via doping of Mn 4+ ions. Besides, as all the energy levels of Mn 4+ ions are around 4 eV these can also be observed in the experimental absorption spectra.